Lifelong Learning through the lens of faculty in Azerbaijan - Ismayilzada, Afag (ADA University, 2023)
Currently, in the field of education, lifelong learning is a crucial concept pointing at knowledge and skill upgrade through formal, informal and non-formal ways. In accordance with National Qualifications Framework of Azerbaijan, this concept is planned to be reinforced in various stages of education. Nevertheless, literature pointed at that there is a lack of awareness and involvement to certain forms of lifelong learning in Azerbaijan. Particularly in higher education stage, findings from studies point at lack of involvement of faculty members to both formal or non-formal learning options (such as, conducting research and participating at developmental programs). This qualitative study examined the way faculty understand and gain new knowledge and skills. The data collected through memoing, review of documents and interviews from 15 faculty members from diverse disciplines. Based on faculty perceptions, definitions of lifelong learning are outlined in three different directions. Findings suggested that in Azerbaijan, faculty members opt for informal learning opportunities due to its less structural and pliable features. Self-study builds up huge part of informal learning and certain personal and institutional level factors hinder faculty engagement with all types of lifelong learning. Only a group of faculties can involve non formal learning opportunities via institutional support, however, formal learning is considered less productive owing to structural and stringent nature, specifically at local PhD programs.
Keywords: Lifelong learning -- Azerbaijan; Higher education -- Faculty development; Educational change -- Azerbaijan; Education